Laser ablation of AgSbS(2) and cluster analysis by time-of-flight mass spectrometry - Houska, Jan; Peña-Méndez, Eladia Maria; Kolár, Jakub; Frumar, Miloslav; Wágner, Tomás; Havel, Josef (Rapid communications in mass spectrometry, 2009)
Thin films of AgSbS(2) are important for phase-change memory applications. This solid is deposited by various techniques, such as metal organic chemical vapour deposition or laser ablation deposition, and the structure of AgSbS(2)(s), as either amorphous or crystalline, is already well characterized. The pulsed laser ablation deposition (PLD) of solid AgSbS(2) is also used as a manufacturing process. However, the processes in plasma have not been well studied. We have studied the laser ablation of synthesized AgSbS(2)(s) using a nitrogen laser of 337 nm and the clusters formed in the laser plume were identified. The ablation leads to the formation of various single charged ternary Ag(p)Sb(q)S(r) clusters. Negatively charged AgSbS(4) (-), AgSb(2)S(3) (-), AgSb(2)S(4) (-), AgSb(2)S(5) (-) and positively charged ternary AgSbS(+), AgSb(2)S(+), AgSb(2)S(2) (+), AgSb(2)S(3) (+) clusters were identified. The formation of several singly charged Ag(+), Ag(2) (-), Ag(3) (-), Sb(3) (+), Sb(3) (-), S(8) (+) ions and binary Ag(p)S(r) clusters such as AgSb(2) (-), Ag(3)S(-), SbS(r) (-) (r = 1-5), Sb(2)S(-), Sb(2)S(2) (-), Sb(3)S(r) (-) (r = 1-4) and AgS(2) (+), SbS(+), SbS(2) (+), Sb(2)S(+), Sb(2)S(2) (+), Sb(3)S(r) (+) (r = 1-4), AgSb(2) (+) was also observed. The stoichiometry of the clusters was determined via isotopic envelope analysis and computer modeling. The relation of the composition of the clusters to the crystal structure of AgSbS(2) is discussed.